(untitled) (The Agriculturists, 2018)
The experiment was conducted in the Horticultural Farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh. Plant growth regulators were applied which had significant effect on yield of sweet pepper (Capsicum annum L.). The experiment consisted of two factors. Factor A: Plant growth regulators (four levels) as G0: Control, G1: Gibberellic Acid (GA3) @ 30 ppm, G2: 4-Chloro Phenoxy Acetic Acid (4-CPA) @ 45 ppm and G3: 4-Chloro Phenoxy Acetic Acid (4-CPA) @ 45 ppm + Gibberellic Acid (GA3) @ 30 ppm and Factor B: Number of spray (three levels) as N0: Control (no spray), N1: two spray, N2: three spray. In case of plant growth regulators, the highest yield (27.77 t/ha) was found from G3 treatment, whereas the lowest (18.87 t/ha) was from G0 treatment. For number of spray the maximum yield (26.0 t/ha) was recorded from N2 treatment, while the minimum yield (19.87 t/ha) was from N0 treatment. The results indicated that the highest yield (31.8 t/ha) was observed from G3N2 treatment combination, while the lowest yield (17.5 t/ha) was from G0N0 treatment combination. Due to combined effect, the highest yield (31.8 t/ha) with net income (Tk/ha 1416558) and BCR (2.46) was observed from G3N2 treatment combination, while the lowest yield (17.5 t/ha) with net income (Tk/ha 433045) and BCR (1.49) from G0N0 treatment combination. Thus, three times spray with (4- Chloro Phenoxy Acetic Acid + Gibberellic Acid) may be recommended for achieving the higher growth, yield and economic benefit of sweet pepper. The Agriculturists 2018; 16(2) 58-64